A Large Real-World Study on the Effectiveness of the Combined Inhibition of EGFR and MET in EGFR-Mutant Non-Small-Cell Lung Cancer After Development of EGFR-TKI Resistance - Liu, Li; Qu, Jingjing; Heng, Jianfu; Zhou, Chunhua; Xiong, Yi; Yang, Haiyan; Jiang, Wenjuan; Zeng, Liang; Zhu, Songlin; Zhang, Yongchang; Tan, Jiarong; Hu, Chengping; et al. (Frontiers in Oncology, 2021)
Background: MET proto-oncogene amplification (amp) is an important mechanism underlying acquired resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI). However, the optimal treatment strategy after acquiring MET-amp-mediated EGFR-TKI resistance remains controversial. Our study compared three treatment strategies for patients with EGFR-mutant NSCLC who were detected with MET-amp at EGFR-TKI progression using next-generation sequencing. Methods: Of the 70 patients included in the study, 38 received EGFR-TKI+crizotinib, 10 received crizotinib monotherapy, and 22 received chemotherapy. Clinical outcomes and molecular profiles were analyzed. Results: The objective response rate was 48.6% for EGFR-TKI+crizotinib group, 40.0% for crizotinib monotherapy group, and 18.2% for chemotherapy group. Patients who received EGFR-TKI+crizotinib had significantly longer progression-free survival than those who received crizotinib or chemotherapy (5.0 vs 2.3 vs 2.9 months, P=0.010), but overall survival was comparable (10.0 vs 4.1 vs 8.5 months, P=0.088). TP53 mutation (58.5%) and EGFR-amp (42.9%) were frequent concurrent mutations of the cohort. Progression-free survival was significantly longer for patients with either concurrent TP53 mutation (n=17) (6.0 vs 2.3 vs 2.9 months, P=0.009) or EGFR-amp (n=13) (5.0 vs 1.2 vs 2.4 months, P=0.016) in the EGFR-TKI+crizotinib group than the other two regimen. Potential acquired resistance mechanisms to EGFR-TKI+crizotinib included EGFR-T790M (n=2), EGFR-L718Q (n=1), EGFR-S645C (n=1), MET-D1228H (n=1), BRAF-V600E (n=1), NRAS-Q61H (n=1), KRAS-amp (n=1), ERBB2-amp (n=1), CDK4-amp (n=1), and MYC-amp (n=1). Conclusion: Our study provides real-world clinical evidence from a large cohort that simultaneous inhibition of EGFR and MET could be a more effective therapeutic strategy for patients with MET-amp acquired from EGFR-TKI therapy.